The other side of innovation : solving the execution challenge - Govindarajan, Vijay; Trimble, Chris (Boston, Mass. : Harvard Business School Pub., 2010)
The authors reveal how to execute an innovation initiative. Regardless of the type of initiative, the crux of the challenge is that business organizations are not designed for innovation; they are designed for ongoing operations. And there are deep and fundamental conflicts between the two.
Introduction: Making innovation happen -- Build the team. Divide the labor ; Assemble the dedicated team ; Manage the partnership -- Run a disciplined experiment. Formalize the experiment ; Break down the hypothesis ; Seek the truth -- Conclusion: Moving on, moving up.
Includes bibliographical references and index.
Keywords: Technological innovations -- Management; Industrial management; Strategic planning